Evaluating options for shifting tax burden to top income earners - Jorge Onrubia; Fidel Picos; María del Carmen Rodado (European Commission, Joint Research Centre (JRC), 2016)
During the last decade, research on income inequality has paid special attention to top income earners. At the same time, top marginal tax rates on upper income earners have declined sharply in many OECD countries. Discussions are still open on the relationship between the increase of the income share of the richest and to what extent the tax burden should be shifted towards top income earners. In this paper we analyse these questions by building and computing a theoretical framework using the decomposition by income groups proposed by Lambert and Aronson (1993) and Alvaredo (2011). We show that for three types of revenue-neutral reforms based on Pfähler (1984) the redistributive effect is always higher than before the reform. When the size of the rich group is sufficiently small we also find that the best option is allocating tax changes proportionally to net income, and the worst doing it proportionally to tax liabilities.
Keywords: D63; H23; H24; 330; inequality; personal income tax; redistribution; top incomes